Inhibitory Effects of Leaves of Guava (Psidium guajava) on TPA-Induced Inflammation and Tumor Promotion in Two-Stage Carcinogenesis in Mouse Skin - Ken Yasukawa; Tomohito Kakegawa (Journal of Pharmacy and Nutrition Sciences, 2015)
Cancer prevention offers the most cost-effective long-term health strategy. The methanol extract of the leaves of guava(Psidium guajava) exhibits marked antitumor activity in an in vivo two-stage carcinogenesis test in mice using 7,12-dimethylbenz[a]anthracene (DMBA) as an initiator and 12-O-tetradecanoylphorbol-13- acetate (TPA) as a promoter. From the active fraction of the methanol extract, five triterpene acids, uvaol (1), ursolic acid (2), corosolic acid (3), asiatic aci (4), and oleanolic acid d (5), were isolated and identified. These compounds were evaluated for their inhibitory effects on TPA-induced inflammation (1 µg/ear) in mice, and showed marked anti-inflammatory effects, with a 50% inhibitory dose of 117–657 nmol/ear. The leaves of guava may therefore be effective for cancer prevention.